Reduced antibacterial property of metallic magnesium in vivo. (9th December 2016) - Hou, Peng; Zhao, Changli; Cheng, Pengfei; Wu, Hongliu; Ni, Jiahua; Zhang, Shaoxiang; Lou, Tengfei; Wang, Chunyang; Han, Pei; Zhang, Xiaonong; Chai, Yimin
Abstract: Magnesium and its alloys have drawn interest as antibacterial biomaterials, owing to their ability to alkalize the surrounding medium during degradation. The antibacterial effect of pure Mg and Mg alloys in vitro has previously been reported. However, the antibacterial property of Mg in vivo might be different because of the apparently dissimilar corrosion characteristics. In this study, pure Mg rods were implanted and bacterial suspension were injected into rat femurs to investigate the antibacterial property of Mg in vivo . The results showed that contrary to the high antibacterial rate in vitro, Mg exhibited a dramatic drop in antibacterial effect in vivo . Bacteria proliferated on the surface of the Mg rods as well as in the femur. Inflammatory cells filled cavities in the cortical bone of the femur, which was demonstrated by histological and micro-CT examination after 2 and 4 weeks of implantation. It is suggested that a reduced corrosion rate in vivo would result in insufficient pH value. In addition, the deposition layer would prevent further corrosion of Mg and provide a favorite site for bacteria adhesion. Hence, the dramatically reduced antibacterial property of Mg needs to be noticed when it is used as a biomaterial.